Response of Sheet Erosion to the Characteristics of Physical Soil Crusts for Loessial Soils - Liu, June; Qi, Xiaoqian; Ma, Chunyan; Wang, Zhanli; Li, Haohong (Frontiers in Environmental Science, 2022)
The influences and quantifications of soil crust traits on the infiltration, hydrodynamic of runoff and erosion rate of sheet erosion under the combined effects of raindrop impacts and sheet flow scouring needs further study. Loessial soil from Loess Plateau was tested to produce different antecedent crusts under simulated rainfall intensities (0.5, 1.0, 1.5, 2.0 and 2.5 mm/min, typical storm intensity in the area), and then the effects of antecedent crusts on sheet erosion processes were quantified at rainfall intensity of 1.5 mm/min. The results showed that the bulk density and hardness of antecedent crusts were higher than that of soil. Particle sizes of crusts were smaller than that of soil at light rain intensity, but larger under heavy rain intensity. The bulk density, hardness and particle size D50 of the antecedent crust were all positively correlated with rainfall intensity, being well described by linear equations (R² > 0.87), while the thickness was negatively linearly correlated with rainfall intensity (R² = 0.88). Although the existence of antecedent crusts could decrease the infiltration and increase the runoff, resulting in the high flow velocity and stream power, antecedent crusts could still effectively reduce sheet erosion. The reductions of average infiltration rate and average erosion rate, and the increases of average flow velocity and stream power all increased with the increment of bulk density of antecedent crust. Relationships could be all well described by linear positive correlations (R² > 0.79). When the bulk density of crust was enhanced by 27~29%, the flow velocity and stream power could be increased by 8~29% and 15~70%, and the sheet erosion could be reduced by 61~73%. The existence of crust could effectively reduce sheet erosion. These results could help understanding the mechanism of erosion process in the presence of physical crusts.